CONTEMPORARY MANAGEMENT OF PEDIATRIC OBESITY: A NARRATIVE REVIEW - Modrzejewska, Wiktoria; Lamparski, Łukasz; Szmit, Grzegorz; Wcisło, Zofia; Basak, Weronika; Chmielewska, Maria; Piekarska, Patrycja; Purwin, Adrianna; Siwiec, Katarzyna; Kułach, Anna; Lach, Karolina; Krok, Gabriela (International Journal of Innovative Technologies in Social Science, 2026)
Background: Pediatric obesity is widely regarded as a heterogeneous, chronic disease associated with metabolic, cardiovascular, and psychosocial consequences. Its increasing prevalence highlights the need for comprehensive, evidence-based management strategies.Aims: This narrative review aims to synthesize current evidence on therapeutic approaches for pediatric obesity, including behavioral management, pharmacologic and surgical treatment, and to highlight emerging treatment directions.Methods: A narrative review was based on a PubMed search, covering studies published through February 2026. Search terms included keywords related to pediatric obesity and related management strategies. Eligible studies included clinical trials, observational studies, systematic reviews, meta-analyses, and clinical guidelines evaluating treatment outcomes in patients aged under 18 years. Evidence was synthesized according to SANRA guidelines.Results: Lifestyle and behavioral interventions persist as the foundation of pediatric obesity management. However, their long-term effectiveness is often suboptimal. Glucagon-like-peptide-1 receptor agonists demonstrate meaningful reductions in BMI along with improvement of obesity-related comorbidities, representing a substantial advancement in pharmacologic therapy. In cases of children with severe obesity not responding to conservative and medical treatment, the most significant weight reduction is provided by metabolic and bariatric surgery. Emerging therapies that target metabolic pathways and the gut microbiome appear promising, yet require additional validation.Conclusions: The treatment and management of pediatric obesity is shifting toward a tailored approach integrating behavioral, pharmacologic, and surgical strategies. Novel pharmacotherapies have significantly expanded treatment options, but long-term safety data and comparative studies remain limited. Multidisciplinary, individualized care is crucial to optimize outcomes in this complex disease.